On the enhanced stability of the guanine-cytosine base-pair radical cation - Clark, Timothy; et al. (Journal of the American Chemical Society, 1996)
Ab initio (UHF/6-31G*) and density functional (Becke3LYP/D95*) calculations have been used to investigate the structures and stabilities of the radical cations of the DNA bases and base pairs. The calculated structures of the base pairs show excellent agreement with crystallographic data. The most easily oxidizable base, guanine, forms a particularly stable radical cation base pair with cytosine, so that the calculated adiabatic ionization potential for the guanine-cytosine hydrogen-bonded complex is about 0.75 eV lower than that of guanine itself. UBecke3LYP/D95*//UHF/6-31G* calculations show that the shift of the central hydrogen-bended proton at N1 of guanine to N3 of cytosine is only slightly endothermic (+1.6 kcal mol(-1)). The product of the corresponding proton shift in the adenine-thymine system is unfavorable by +14.1 kcal mol(-1). These results suggest that the guanine-cytosine radical cation represents even more of a thermodynamic sink in oxidized DNA than might be concluded from the ionization potentials of the individual bases, and that it enjoys about 7.3 kcal mol(-1) extra stabilization from the central low-barrier hydrogen bond.